RATIO OF NUTRIENT AND DIATOM-DINOFLAGELLATE COMMUNITY IN SPERMONDE WATERS, SOUTH SULAWESI - Andriani Nasir; Muhammad Lukman; Ambo Tuwo; . Nurfadilah (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Runoff of nutrients (N, P, Si) from the mainland would disrupt the balance of nutrients in the waters resulted in changing microalgae communities composition, especially between diatom and dino-flagellate (Dia/Dino). This study was aimed to analyze the relationship of nutrient ratios (N/P, N/Si, Si/P) in the waters, to the density ratio of the Dia/Dino in the coastal and marine waters of Spermonde archipelago, South Sulawesi, Indonesia, which experience nutrient enrichment. Nutrients and phyto-plankton samples were collected from the coastal waters of Tallo, Maros, Pangkep, and seawaters of Spermonde in three seasons (transition, wet, and dry). The results showed the average value (± stan-dard deviation) of Dia/Dino ratio in the coastal and sea waters is 1422±1742 and 1174±1290 in the transition season; 238±205 and 1039±2264 in the dry season; and 153±270 and 72±71in the rainy season. Meanwhile, in the marine waters the ratio of Dia/Dino ranges between 1 and 9839. The ratio of Dia/Dino was not different significantly (p>0,05) by spatial and temporal, but Dia/Dino ratio was different significantly (p<0,05) on the ratio of nutrients in coastal waters, where the value of N/Si ratio tends to ignite monospesies enrichment diatom (Chaetoceros) with a variant of 70,4%. Keywords: nutrient ratios, diatom, dinoflagellate, coastal, Spermonde